PRESENCE AND PLACE OF THE SACRED DIMENSION IN THE CHICO BUARQUE'S WORKS: EDUCATIONAL AND LITERARY ASPECTS IN LYRICAL ANALYSIS OF FOUR SONGS - Constantino, Paulo Roberto Prado [UNESP]; Camargo Filho, Jorge Geraldo de (Centro Univ Nove Julho, 2024)
This article aims to develop a lyrical analysis of the compositions by Chico Buarque, focusing on the presence and place of the sacred in the lyrics of four of his songs, Dueto, C & aacute;lice, Salmo, and Sinh & aacute;. Employed a documentary and bibliographical research, supported by a framework based on multidisciplinary studies. Buarque's songs, as works that merge the musical, literary, and poetic realms, exhibit thematic richness and a complex plot, intertwining cultural, religious, and historical elements to comment on aspects of Brazilian society. By examining this poetic dimension in songs, the study not only contributes to revisiting the artist's oeuvre but also provides a pathway for music education, access to literature, and literacy, which can be beneficial for both basic and specialized education.
Keywords: music education; analysis; composition; literature; Chico Buarque